MODEL PENYELESAIAN SENGKETA LINGKUNGAN MELALUI LEMBAGA ALTERNATIF - Mr. Absori; Khuzaefah Dimyati; Kelik Wardiono (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
Resolving environmental dispute through court litigation often ends up with failure. As a consequence, society in ccoperation with Non-Governmental Organization (NGO) and environmental organization prefer to use Alternative Dispute resolution (ADR) to reslove environmental dispute. In this regard, mediation is often chosen by the parties as it promotes a “win-win solution”. Moreover, mediation offers efficient, cheap and fast dispute resolution process. However, Indonesian law has not adequately accomodated the use of ADR in environmental dispute. As a consequence, the problem of legal certainty often come up. In order to overcome this situation, it is important to develop a mediation process that ensures the legal certainty for both of the disputants. This can be done by developing a mediation forum which is legalized by court.